Alfred H. Barr, Jr. : and the intellectual origins of the Museum of Modern Art - Kantor, Sybil Gordon (Cambridge : MIT press, 2002)
Prologue: Knowing Alfred Barr -- Ch. 1. The Princeton Years -- Ch. 2. The Fogg Method and Paul J. Sachs: Barr and his Harvard Mentor -- Ch. 3. Barr as Teacher, 1925 to 1927 -- Ch. 4. The Little Magazine and Modernism at Harvard -- Ch. 5. The European Trip -- Ch. 6. Modernism Takes Its Turn in America -- Ch. 7. Architecture, Barr, and Henry-Russell Hitchcock -- Ch. 8. Philip Johnson and Barr: Architecture and Design Enter the Museum -- Ch. 9. The Directorship at Full Throttle.
CCS Gent
boek
Keywords: Barr, Alfred H. Jr